Bahasa Anak JakSel: A Sociolinguistics Phenomena - Dzakiyyah Rusydah (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2020)
Bahasa Anak JakSel is the phenomena that came up around September 2018. The appearance becomes a yammer because that phenomena contains Bahasa Indonesia and English. The special thing about this phenomenon is not only the combining language, but there are also some commonly used English words in it. English words which are repeatedly used to gather with Bahasa Indonesia. In this research, Bahasa Anak JakSel is chosen to be analyzed through Sociolinguistics theory. This research has two focuses, first is the commonly used English words according to the informants, and second is the reason behind that phenomenon. The data is taken by handing-out questionnaire (Google form) through many online social media platforms. The informants of this research are the origin or have live for a long time in Jakarta as the original language of Bahasa Anak JakSel. This research is done by Sociolinguistics perspective to analyze the languages and the reason behind it. This research uses qualitative method in order to analyze the data and explaining the result in descriptive. The aim of this research is to find out the commonly used English words and some reasons of the informants use Bahasa Anak JakSel. The results of this research are in Bahasa Anak JakSel the commonly used English words divided into some sub groups like pronoun, adverb, adjective, verb, acronym, redundant words and phrase, and untranslatable words. Those are commonly used English words appeared in Bahasa Anak JakSel has some reasons behind, such as language pride, part of social demands, untranslatable word in Bahasa Indonesia, and enriching the English vocabulary.